Aggregate Demand and the Top 1 Percent - Auclert, Adrien; Rognlie, Matthew (American Economic Review, 2017)
There has been a large rise in US top income inequality since the 1980s. We merge a widely studied model of the Pareto tail of labor incomes with a canonical model of consumption and savings to study the consequences of this increase for aggregate demand. Our model suggests that the rise of the top 1 percent may have led to a large increase in desired savings and can explain a 0.45pp to 0.85pp decline in long-run real interest rates. This effect arises from both a wealth effect at the top and increased precautionary savings from declines lower in the income distribution.